Selection and Validation of Reference Genes for RT-qPCR Normalization in Bradysia odoriphaga (Diptera: Sciaridae) Under Insecticides Stress - Fu, Haiyan; Huang, Tubiao; Yin, Cheng; Xu, Zhenhua; Li, Chao; Liu, Chunguang; Wu, Tong; Song, Fuqiang; Feng, Fujuan; Yang, Fengshan (Frontiers in Physiology, 2022)
Bradysia odoriphaga (Diptera: Sciaridae) is the most serious root maggot pest which causes substantial damage to the Chinese chive.Organophosphate (OP) and neonicotinoid insecticides are widely used chemical pesticides and play important roles in controlling B. odoriphaga. However, a strong selection pressure following repeated pesticide applications has led to the development of resistant populations of this insect. To understand the insecticide resistance mechanism in B. odoriphaga, gene expression analysis might be required. Appropriate reference gene selection is a critical prerequisite for gene expression studies, as the expression stability of reference genes can be affected by experimental conditions, resulting in biased or erroneous results. The present study shows the expression profile of nine commonly used reference genes (EF-1α, ACT, EF-2α, G6PDH, GAPDH, RPL10, RPS3, UBC, and TUB) was systematically analyzed under insecticide stress.Moreover, we also evaluated their expression stability in other experimental conditions, including developmental stages, sexes, and tissues.Five programs (NormFinder, geNorm, BestKeeper, RefFinder and ∆Ct) were used to validate the suitability of candidate reference genes.The results revealed that the most appropriate sets of reference genes were RPL10 and ACT across phoxim; ACT and TUB across chlorpyrifos and chlorfluazuron; EF1α and TUB across imidacloprid; EF1α and EF2α across developmental stages; RPL10 and TUB across larvae; EF1α and ACT across tissues; and ACT and G6PDH across sex.These results will facilitate the standardization of RT-qPCR and contribute to further research on B. odoriphaga gene function under insecticides stress.